If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3w + -2) = 57 Reorder the terms: 3(-2 + 3w) = 57 (-2 * 3 + 3w * 3) = 57 (-6 + 9w) = 57 Solving -6 + 9w = 57 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 9w = 57 + 6 Combine like terms: -6 + 6 = 0 0 + 9w = 57 + 6 9w = 57 + 6 Combine like terms: 57 + 6 = 63 9w = 63 Divide each side by '9'. w = 7 Simplifying w = 7
| x+x+10+44=90 | | 2t+8=t+14 | | 3x-4[2x-7/2]=4 | | 1/4z=-6 | | (6x+9)=2 | | -9x+4y=16 | | 2k-1/2=-3/2 | | 100/54 | | (x+4)(x-7)=70 | | 5x-7=-46 | | 5+3x=-16+9x-9x | | 2.5(4-2-8)=50 | | 91=4x+1.5x+x | | -7=y/-7 | | 1/4z=-5 | | 3q^2=10-2q^2 | | 2(w-3)=w-5 | | 5g^2-9g-2=0 | | (x+88)-5x=40 | | 5*x=27/5 | | 8x+4y=56 | | (-x+2)=4 | | Y^2=2-y^2 | | 5n^2+4n=28 | | 3x^3-5x^2-27x+45=0 | | -10n+7=-18-5n | | 7.7=(2.1-7m) | | 13.5/3 | | -18n+18=-16n-2 | | 1/2x-5=13 | | 1*x=27/5 | | 140=15x+20 |